Relapse of cervical cancer 12 years after the treatment - Enes, Pedro Vieira; Brandão, Pedro; Rocha, Juliana; Pinto, Ana Rita; Costa, Fernanda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Cervical cancer is the third most common gynecologic cancer in women and it remains one of the main causes of death. With rare exceptions, it results from an HPV infection and about 5% of this infection will culminate in the development of CIN 2 or CIN 3 lesions. After treatment with surgery or radiotherapy, 10 to 20% of the patients will have a relapse and/or metastases usually in the first two years after completing their treatment. In this article, we present a clinical case of a lymph node relapse 12 years after treatment in a 43-year-old patient with a microinvasive cervical cancer history, Figo stage IA1, without lymphovascular invasion.